Pengaruh Kepuasan Kerja dan Motivasi terhadap Kinerja Perawat di Rumah Sakit X Denpasar - Ni Nyoman Sintari, Silvia; Gede Subhaktiyasa, Putu (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
Job satisfaction is an attitude of achievement and love for one's work, work motivation is a stimulus for carrying out work, performance is the achievement of work results. These three things are interrelated, this research aims to determine the relationship between job satisfaction and motivation on performance. Non-experimental research method, correlational study with a cross-sectional approach. The research location is Hospital X Denpasar. The population of all nurses at Hospital X Denpasar is 61 people, with total sampling, so the total sample is 61 people. Using the Job Satisfaction Questionnaire, Nurse Motivation and Performance. The research results based on gender, the majority were women, 70%, the majority were educated as nurses, 75%. Nurse Job Satisfaction is highest with a very high category of 75.4%. Most nurses' motivation is in the very high category, 96.7%. Nurse performance is 100% very high. The results of the analysis using rank spearment show that there is a relationship between motivation and nurse performance (p value: 0.034) and there is a relationship between job satisfaction and performance (p value: 0.000). These results indicate that hospital x has maintained nurses' job satisfaction, so that nurses have good motivation to achieve good performance. It is recommended to get good performance in order to maintain employee job satisfaction.